2017
DOI: 10.1080/10641963.2017.1411500
|View full text |Cite
|
Sign up to set email alerts
|

Association study ofFOXP3gene and the risk of 0020 pre-eclampsia

Abstract: Pre-eclampsia (PE) is a multifactorial pregnancy disorder, with serious consequences for both the mother and the fetus. Despite intense studies, the pathophysiology of PE remains enigmatic. Previous studies suggested that Treg dysfunction is involved in the pathogenesis of PE. We hypothesized that functional variants of the FOXP3 gene might be associated with PE via dysregulation of Treg cells. Of the 276 subjects, we genotyped three variants of FOXP3 by PCR-RFLP and Tetra ARMS-PCR methods. The genotypic frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Gholami et al in Tehran investigated the role of rs2232365 and rs3761548 polymorphisms. For the first polymorphism they found AG genotype as a risk factor and for the second polymorphism they found AA genotype as a protecting factor (22). Although our study had been performed in Iran, however Lur population of Iran showed unique results even in comparison to other Iranian populations.…”
Section: Discussionmentioning
confidence: 62%
“…Gholami et al in Tehran investigated the role of rs2232365 and rs3761548 polymorphisms. For the first polymorphism they found AG genotype as a risk factor and for the second polymorphism they found AA genotype as a protecting factor (22). Although our study had been performed in Iran, however Lur population of Iran showed unique results even in comparison to other Iranian populations.…”
Section: Discussionmentioning
confidence: 62%
“…For instance, it was illustrated that FOXP3 rs3761548 was linked to the susceptibility of PE patients. 10,11 In contrast, several other studies revealed that no obvious relationship was found between this SNP and the risk of PE. [27][28][29]31 Furthermore, studies regarding the effects of rs2232365 and rs2280883 polymorphisms on the risk of PE also exhibited inconsistent conclusions.…”
Section: Introductionmentioning
confidence: 73%
“…11,25,26 Recently, growing researches investigated the relationship of FOXP3 polymorphisms with PE risk, among which single nucleotide polymorphisms (SNPs) of -3279C/A (rs3761548), -925A/G (rs2232365), rs4824747, -3499T/C (rs3761547) and IVS9+459T/C (rs2280883) were mostly investigated. [9][10][11][27][28][29][30][31] However, currently available studies did not reach any unanimous conclusions so far. For instance, it was illustrated that FOXP3 rs3761548 was linked to the susceptibility of PE patients.…”
Section: Introductionmentioning
confidence: 99%
“…We find FOXP3 rs2232365 a novel function of affecting the TG/HDL level in Chinese pregnant women. FOXO3 rs3761548 was also reported as a risk factor to immune-related pregnancy complications [35] and an important contributor for the progression of PE in Iranian women [39]. While no associations between SNP rs3761548 and preeclampsia were found either in Iranian women [40] or the Turkish population [41].…”
Section: Summary Of Key Resultsmentioning
confidence: 99%